(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The objectives of the study are to analyze the transients in heated pipelines using the finite element method and the achievement of reduction of energy losses during transportation of liquids in pipelines with electric heating systems by determining the optimal operating conditions and design parameters of the pipeline and electric heating system